2005
DOI: 10.1074/jbc.m501571200
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Early Gene X1 (IEX-1) Is Organized in Subnuclear Structures and Partially Co-localizes with Promyelocytic Leukemia Protein in HeLa Cells

Abstract: Immediate early gene X1 (IEX-1) represents a stress response gene involved in growth control and modulation of apoptosis. Here, we report a detailed analysis of IEX-1 with respect to its intracellular localization. By means of confocal laser scanning microscopy, a green fluorescent protein-IEX-1 fusion protein transfected into HeLa cells, as well as endogenous IEX-1, could be detected in distinct subnuclear structures. This particular subnuclear localization of IEX-1 was not observed with a green fluorescent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Conversely, a K60A/R63A mutant with an altered nuclear localization sequence showed no apoptosis-enhancing effects over background (Fig. 4A), in contrast to its insignificance in cell survival, confirming early investigation (26). Thus, our results delineate distinct regions of IEX-1 for its anti-and pro-apoptotic activities and as a corollary, discrete nonoverlapping mechanisms are likely to mediate these two opposing activities conferred by IEX-1.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Conversely, a K60A/R63A mutant with an altered nuclear localization sequence showed no apoptosis-enhancing effects over background (Fig. 4A), in contrast to its insignificance in cell survival, confirming early investigation (26). Thus, our results delineate distinct regions of IEX-1 for its anti-and pro-apoptotic activities and as a corollary, discrete nonoverlapping mechanisms are likely to mediate these two opposing activities conferred by IEX-1.…”
Section: Resultssupporting
confidence: 64%
“…Additionally, N-linked glycosylation and phosphorylation as well as the C-terminal sequence of IEX-1, are all crucial for anti-apoptosis activity of IEX-1, but these structures appear to exert no discernible role in pro-apoptosis. On the contrary, mutation of nuclear localization sequence, despite its importance in apoptosis, did not impede IEX-1-mediated cell survival (26). IEX-1-mediated cell survival is found to correlate well with its ability of reducing intracellular ROS formation either at basal levels or immediately after apoptotic stimulation.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…In the present study, the expression of at least two proteins, S-100 and GFAP were stimulated by overexpression of IEX-1. A recent detailed subcellular localization analysis [Kruse et al, 2005] has revealed that IEX-1 is recruited to and exported from the nucleus. This typical movement to and from nucleus is common for the molecules involved in the regulation of gene transcription or reorganization of nuclear proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In some cell types, expression of IEX-1 promotes apoptosis (1), while in others, it is protective (92). The protein is found to be associated with ND10 domains (40) and shuttles between the nucleus and the cytoplasm in response to certain stimuli (38). Even though IEX-1 mRNA is up-regulated and stabilized in HSV-infected cells, Taddeo and colleagues report that the protein is not detectable later than 1 h after infection (85), implying that the protein is degraded and/or its mRNA is not translated.…”
Section: Icp27mentioning
confidence: 99%